A vector analyzer for observing millimeter-submillimeter resonances - Goy, P; Caroopen, S; Gross, M; Ardavan, A; Edwards, R; Rzepniewski, E; Singleton, J (IEEE, 2000)
The described microwave system for scientific applications is a Vector Analyzer based on an original principle allowing its use up to very high frequencies. Vector measurement of resonances is extremely effective and accurate, since the determination of resonance position and width does not depend on the lineshape, which can vary strongly with experimental conditions. Examples of resonance observations between 20 and 800 GHz are presented. They were observed with frequency variation in microwave resonant structures (cavities, interferometers) and with magnetic field variation in semiconductors or in magnetic materials (cylotron resonance, electron spin resonance). © 2000 IEEE.